Literasi Keuangan Digital Dan Kapabilitas Dalam Pengambilan Keputusan Keuangan Mahasiswa Kota Semarang - Kusuma, Septian Yudha; Widyarti, Maria Theresia Heni; Rokhimah, Zulaika Putri; Hartono, Hartono; Handayani, Jati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze further the impact of digital financial literacy on financial decision-making and financial capability on financial decision-making, as well as analyse the mediating role of financial capability in the influence of digital financial literacy on financial decision-making. The sample obtained in this research was 251 respondents using simple random and snowball sampling techniques. The research results show that digital financial literacy has a significant positive effect on financial capabilities and financial capability. At the same time, financial capability is also proven to have a significant positive effect on financial decision-making. Finally, testing the mediating role of financial capability on the relationship between digital financial literacy and financial decision-making also proved to have a significant effect.